2004
DOI: 10.1139/e04-004
|View full text |Cite
|
Sign up to set email alerts
|

Variations in mixed-layer illite/smectite diagenesis in the rift and post-rift sediments of the Jeanne d'Arc Basin, Grand Banks offshore Newfoundland, Canada

Abstract: Mixed-layer illite/smectite (I/S) clays were analyzed from 22 deep exploration wells from the Jeanne d'Arc Basin on the Grand Banks offshore Newfoundland, the host of large commercial hydrocarbon accumulations discovered in the last two and a half decades. The fine fraction of the clays (<0.1 µm) consists mainly of mixed-layer I/S with minor amounts of kaolinite, illite, and chlorite. Smectite and (or) smectite-rich I/S clays were supplied to the Jeanne d'Arc Basin from Upper Jurassic to Tertiary times. Sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
0
22
1
Order By: Relevance
“…8). These temperatures are also greater than those described in the literature (Abid et al, 2004). Such high values may be related to the type of rocks (marls and marly limestones) in which the illitization took place.…”
Section: Thermal Modelling and Clay Mineralogycontrasting
confidence: 44%
See 2 more Smart Citations
“…8). These temperatures are also greater than those described in the literature (Abid et al, 2004). Such high values may be related to the type of rocks (marls and marly limestones) in which the illitization took place.…”
Section: Thermal Modelling and Clay Mineralogycontrasting
confidence: 44%
“…In this well, the disappearance of smectite (R0), which marks the transition between zones R0 and R1, took place at a maximum temperature of 160ºC (Fig. 8), much higher than the values of 75À120ºC reported in the literature (Hoffman & Hower, 1979;Ś rodoń & Eberl, 1984;Schegg & Leu, 1996;Uysal et al, 2000b;Abid et al, 2004).…”
Section: Thermal Modelling and Clay Mineralogymentioning
confidence: 55%
See 1 more Smart Citation
“…It has been suggested that the temperature that reflects the appearance of R1 I/S during the smectite illitization process is generally around 100 °C while the transition temperature from R1 to R3 I/S can be up to ca. 180 °C [48,50,[53][54][55]. In this study, most of the studied samples have the R1 ordered I/S, except for only one sample that has the R3 ordered I/S (Table 1) indicating that the paleo-diagenetic temperature for the studied samples could have been up to 180 °C but for most of the samples, this value ranges from 100 to 180 °C.…”
Section: Implications For Paleo-diagenetic Temperaturementioning
confidence: 95%
“…Temperature and fluid chemistry thus should be the dominant factors that would have influenced the formation of I/S in this study. Many studies have focused on the diagenetic temperature during the burial process, using the evolution of smectite illitization (especially the percentages of smectite layers within I/S) [48,50,[53][54][55]. In the XRD patterns for the EG-saturated clay fractions, as smectite layers decrease in I/S, the peaks at 9 Å, as well as peaks at 5 Å, become sharp and narrow showing a trend towards illite and indicating a progressive increment in temperature (Figure 7).…”
Section: Implications For Paleo-diagenetic Temperaturementioning
confidence: 99%